2015
DOI: 10.1177/0004867415616695
|View full text |Cite
|
Sign up to set email alerts
|

Mortality associated with anxiolytic and hypnotic drugs—A systematic review and meta-analysis

Abstract: This meta-analysis suggests that hypnotics or anxiolytics drugs use is associated with increased mortality and hence should be used with caution. Future studies focused on underlying mechanism of increased mortality with hypnotics or anxiolytics use are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 43 publications
5
41
0
1
Order By: Relevance
“…However, this study showed no significant association between use of hypnotics and incidence of ESKD (Table 3). A large number of cohort studies have reported users of hypnotics to be at risk of early death (41,42), suggesting that hypnotics should be prescribed with great caution in patients with CKD with short sleep duration. The clinical effects of modification of sleep duration on kidney function need to be examined in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study showed no significant association between use of hypnotics and incidence of ESKD (Table 3). A large number of cohort studies have reported users of hypnotics to be at risk of early death (41,42), suggesting that hypnotics should be prescribed with great caution in patients with CKD with short sleep duration. The clinical effects of modification of sleep duration on kidney function need to be examined in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Recent cohort studies suggest an increased risk of exacerbations in benzodiazepine users with asthma and a higher likelihood of episodes of pneumonia and related mortality . A recent systemic review also highlighted an overall increased risk of all‐cause mortality in benzodiazepine users . Inappropriate use of benzodiazepines in Australia has been recently reported to lead to high costs of managing adverse events in residential aged care facilities …”
Section: Introductionmentioning
confidence: 99%
“…Since that time evidence of broad-ranging harms resulting from long-term BDZ use has continued to grow, including cognitive deficits [8][9][10], reductions in quality of life [11][12][13], depression [14][15][16], risk of suicide [17], risk for road accidents [18,19], and specific to older adults-the risk of falls [20][21][22], developing dementia [23][24][25], and of mortality [26][27][28]. Short-term, paradoxical effects such as increased anxiety, agitation, disinhibition, and aggression have also been observed [29,30].…”
Section: Costs Of Benzodiazepine Usementioning
confidence: 99%